The Development of Research-Based Learning Tools with a STEM Approach to Improve Metaliteracy Skills to Solve Rainbow Vertex Anti-magic Coloring Problems - Qurrotul A’yun; Slamin Slamin; Dafik Dafik (Pancaran Pendidikan, 2022)
Metaliteracy is the framing and strengthening of information literacy based on critical and creative thinking. Metaliteracy indicators include generating, combining, using, participating, sharing, and collaborating. To implement higher-order thinking skills, we implement research-based learning with a STEM approach. To develop the students’ metaliteracy, educators should also equip the learning process by learning materials. In this study, we developed RBL-STEM learning materials to improve students' metaliteracy skills. The learning materials that have been developed are considered to be valid, effective, and practical. The validity score obtained in each materials is 3.5 for the Lesson Plan, 3.54 for the Student Worksheet, and 3.63 for the Learning Outcomes Test.